Optical properties of nanostructures - Miloslavsky, V.K.; Ageev, L.A.; Makovetsky, E.D.; Maskevich, S.A. (Functional Materials, 2008)
The paper is a brief review of optical properties of nanostructures containing metal nanoparticles. There is a deduction of some simple formulae describing optical spectra of composites containing small particles of various form. Comparison of theoretical and experimental data has been carried out. Conclusions following Mie theory of diffraction on spheres of various diameters and dielectric permittivities are discussed. Various examples of applications of nanoparticles and their influence on surrounding media are given.